1989
DOI: 10.1002/macp.1989.021900801
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐opening polymerization of carbohydrate‐derived dialkoxyoxolanes. Approaches to functionalized poly(oxytetramethylene)s

Abstract: A series of various cis-3,4-diacyloxy-and dialkyloxy-oxolanes (4 to 14) as well as the oxolanes 16 and 17 were prepared. Ring-opening polymerizations of the dialkyloxy derivatives 4,6, and 11 using the super-acids FS0,H and CF3S0,H led to novel functionalized poly[oxy(2,3-dialkyloxytetramethkene)]~. The reaction parameters were thoroughly studied, and optimum conditions lead to a DP, up to 35. All polyethers were fully assigned by polymer analytical procedures such as GPC, osmometry, 'H NMR spectroscopy and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The extension of the polymerization time led to a decrease in M w,SLS as a comparison between runs 2 and 4. A similar result was reported in the ring-opening polymerization of 1,4-anhydro-2,3-di-O-methylerythritol (6a) and 1,4-anhydro-2,3-di-O-ethylerythritol using CF 3 SO 3 H and FSO 3 H. 11,12 In the polymerization of 1a using FSO 3 H as a catalyst, the M w,SLS was low as 1.0 × 10 4 , which should be related to the lower acidity of FSO 3 H (pK a ) -12.60) in contrast to CF 3 SO 3 H (pK a ) -19.12). 12 The M w,SLS values of the polymer (2b) prepared from 1b were lower than those of 2a; i.e., for the [1]/[CF 3 SO 3 H] molar ratio of 20 at 80 °C for 240 h, the M w,SLS value of 2b was 22.6 × 10 4 , while that of 2a was 51.0 × 10 4 .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The extension of the polymerization time led to a decrease in M w,SLS as a comparison between runs 2 and 4. A similar result was reported in the ring-opening polymerization of 1,4-anhydro-2,3-di-O-methylerythritol (6a) and 1,4-anhydro-2,3-di-O-ethylerythritol using CF 3 SO 3 H and FSO 3 H. 11,12 In the polymerization of 1a using FSO 3 H as a catalyst, the M w,SLS was low as 1.0 × 10 4 , which should be related to the lower acidity of FSO 3 H (pK a ) -12.60) in contrast to CF 3 SO 3 H (pK a ) -19.12). 12 The M w,SLS values of the polymer (2b) prepared from 1b were lower than those of 2a; i.e., for the [1]/[CF 3 SO 3 H] molar ratio of 20 at 80 °C for 240 h, the M w,SLS value of 2b was 22.6 × 10 4 , while that of 2a was 51.0 × 10 4 .…”
Section: Resultssupporting
confidence: 85%
“…13 C NMR (D2O) δ: 72.61 (C1 and C4), 71.08 (C2 and C3), 63.25 ppm (CH2OH, terminal). 11 and 1,4-anhydro-2,3di-O-methyl-L-threitol (6b) 12 were synthesized from erythritol and L-threitol, respectively, using a procedure similar to that reported by Thiem. 6a: Yield, 76.1%.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, in the polymerization of 4a using FSO 3 H as a catalyst, the M w;SLS was as low as 1.0 Â 10 4 , which should be related to the lower acidity of FSO 3 H (pK a ¼ À12.6) in contrast to CF 3 SO 3 H (pK a ¼ À19.1). [54] The lower M w;SLS value (maximum 2.3 Â 10 5 ) of 5b compared to that of 5a should be caused by the difference in the ring strain effect between 4a and 4b; that is, the ring-opening reaction of the tetrahydrofuranyl ring in 4a proceeded more easily than that of 4b.…”
Section: Synthesis Of a Hyperbranched Carbohydrate Polymer By Ring-opmentioning
confidence: 99%
“…On the other hand, Thiem et al reported the synthesis of a polymeric carbohydrate by ring-opening polymerization of carbohydrate-derived dialkoxyoxolanes and 1,4:2,5: 3,6-trianhydro-D-mannitol. [10][11][12] Recently, we presented the cyclopolymerization of 1,2: 5,6-dianhydrohexitol as a new method for synthesizing polymeric carbohydrates. [13][14][15][16][17][18][19][20] 3,4-Di-O-alkyl substituted 1,2:5,6-dianhydro-D-mannitols and L-iditol were found to polymerize using cationic initiators, and the resulting polymers consisted of 2,5-anhydro-D-glucitols as the main repeating cyclized units, together with other cyclic units as minor components.…”
Section: Introductionmentioning
confidence: 99%
“…These polysaccharides are termed artificial polysaccharides. On the other hand, Thiem et al reported the synthesis of a polymeric carbohydrate by ring-opening polymerization of carbohydrate-derived dialkoxyoxolanes and 1,4:2,5:3,6-trianhydro- d -mannitol. …”
Section: Introductionmentioning
confidence: 99%